Countermeasures Against the Strategic Use of Evidence Technique: Effects on Suspects' Strategies. Issue 2 (14th October 2015) - Luke, Timothy J.; Hartwig, Maria; Shamash, Benjamin; Granhag, Pär Anders
Abstract: As the Strategic Use of Evidence (SUE) technique becomes more widely taught to practitioners, it is important to investigate possible countermeasures to the technique. It is possible that guilty suspects who are aware of the SUE technique will employ forthcoming verbal strategies to make themselves appear innocent. Mock suspects committed a richly detailed simulated transgression (or a benign analogue) and were interviewed about their activities. Prior to questioning, some suspects received information about SUE tactics the interviewer was likely to use. Guilty suspects who were informed about the SUE technique employed more verbally forthcoming strategies than their uninformed counterparts. Guilty suspects who were given SUE information also reported planning for the interview in different ways. However, guilty‐informed suspects did not become as forthcoming as innocent suspects overall. In sum, it appears that information about the SUE technique induces guilty suspects to alter their strategies, but only to a relatively small degree.Copyright © 2015 John Wiley & Sons, Ltd.